ANALYSIS OF PRESCRIPTIONS OF ANABOLIC AGENTS DISPENSED BY COMMERCIAL PHARMACIES IN THE MUNICIPALITY OF FORTALEZA – CEARÁ - De Oliveira Junior, Valdir Augusto; Gonçalves Medina, Lígia Lucena; Holanda , Rose Lídice (Cadernos ESP, 2023)
Analyze the prescription of anabolic steroids dispensed by commercial pharmacies in the city of Fortaleza. Retrospective study with a quantitative approach, based on special control prescriptions that commercial pharmacies retain when dispensing anabolic-based drugs. The drug deposteron was the most prescribed both by prescriptions and by total amount of prescriptions, the majority being prescribed by physicians without a specialty described in the prescription, for male patients with ICD of hormonal dysfunction linked to the lack of the hormone testosterone, therefore being in accordance with the use determined in the medication leaflet. The results of this study found the relevance of documentary analyzes of prescriptions held in pharmacies, and these prescriptions should be monitored for decision-making by the competent bodies when determining the increase in prescription.
Keywords: Anabolic steroids; Prescriptions; Dispensation; Pharmacy